Health System Preparedness, Response, and Incidence of Dengue in District Mianwali : Health System Preparedness, Response, and Incidence of Dengue - Naseem, Fatima; Khattak, Muhammad Iftikhar; Rashid, Faisal; Nasim, Samia; Waheed, Mustafa Khalid; Mustafa, Javaria (Pakistan Journal of Health Sciences, 2024)
Dengue is a mosquito-borne viral infection caused by the dengue virus. It has 4 different serotypes and is mainly spread by Aedes mosquitoes. The disease is a significant public health problem worldwide. Objective: Assess district health system preparedness for Dengue outbreaks, identify gaps, strengthen surveillance, and determine incidence post-preventive measures. Methods: The study was a mixed-method design, using both qualitative and quantitative approaches. A cross-sectional design was used to assess the incidence of dengue. Results: A total of 118 participants were selected for questionnaire-based interviews out of which 47.9% were male and 51.3% were females. The average age of the participants was 38.58 ± 9.63 with a minimum age of 24 years and minimum age of 55 years was observed. Overall 8.4% of the participants belonged to the Supervisor cadre, 5.9% were entomologists, 32.8% were CDC supervisors and 52.1% were clinical doctors. Most healthcare professionals find it easy to diagnose and report a case of dengue fever. Only 0.85% of the participants felt it very difficult to diagnose and report a dengue case, 45.76% felt somewhat easy and 44.07% felt very easy in reporting a dengue case. Some of the participants 9.32% neither felt it easy nor difficult to report dengue cases. Conclusions: Punjab, Pakistan’s dengue surveillance system has improved but needs further enhancements in case detection, reporting, communication, and stakeholder collaboration. The province has established dengue monitoring units and implemented a comprehensive reporting system.